Differential expression of salivary proteins between susceptible and insecticide-resistant mosquitoes of Culex quinquefasciatus. - Innocent Djegbe; Sylvie Cornelie; Marie Rossignol; Edith Demettre; Martial Seveno; Franck Remoue; Vincent Corbel (PLoS ONE, 2011)
BACKGROUND: The Culex quinquefasciatus mosquito, a major pest and vector of filariasis and arboviruses in the tropics, has developed multiple resistance mechanisms to the main insecticide classes currently available in public health. Among them, the insensitive acetylcholinesterase (ace-1(R) allele) is widespread worldwide and confers cross-resistance to organophosphates and carbamates. Fortunately, in an insecticide-free environment, this mutation is associated with a severe genetic cost that can affect various life history traits. Salivary proteins are directly involved in human-vector contact during biting and therefore play a key role in pathogen transmission. METHODS AND RESULTS: An original proteomic approach combining 2D-electrophoresis and mass spectrometry was adopted to compare the salivary expression profiles of two strains of C. quinquefasciatus with the same genetic background but carrying either the ace-1(R) resistance allele or not (wild type). Four salivary proteins were differentially expressed (>2 fold, P<0.05) in susceptible (SLAB) and resistant (SR) mosquito strains. Protein identification indicated that the D7 long form, a major salivary protein involved in blood feeding success, presented lower expression in the resistant strain than the susceptible strain. In contrast, three other proteins, including metabolic enzymes (endoplasmin, triosephosphate isomerase) were significantly over-expressed in the salivary gland of ace-1(R) resistant mosquitoes. A catalogue of 67 salivary proteins of C. quinquefasciatus sialotranscriptome was also identified and described. CONCLUSION: The "resistance"-dependent expression of salivary proteins in mosquitoes may have considerable impact on biting behaviour and hence on the capacity to transmit parasites/viruses to humans. The behaviour of susceptible and insecticide-resistant mosquitoes in the presence of vertebrate hosts and its impact on pathogen transmission urgently requires further investigation. DATA DEPOSITION: All proteomic data will be deposited at PRIDE (http://www.ebi.ac.uk/pride/).